Anesthetic management in a patient with acute cervical spinal cord injury in neurogenic shock for humerus plating - Ideal timing and anesthetic technique - Vinod Krishnagopal; Raj Murugan; Sharanya Krishnakumar; M Thilak (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Traumatic acute cervical spinal cord injury (ACSCI) often presents with non-emergent coexisting injuries, which might need surgical intervention. The ACSCI affects multiple systems including respiratory, cardiovascular, and neurological systems, which pose a great challenge to the treating anesthesiologist. The ideal time and anesthetic technique for non-emergent surgeries following ACSCI is not clear. Maintenance of mean arterial blood pressure between 85 and 90 mmHg for 7 days following spinal cord injury would improve the outcome. The secondary injury peaks at 4–6 days following the primary cord injury. Considering the above-mentioned factors, the non-emergent procedures could be performed after the seventh day following an injury of the spinal cord. Regional anesthesia (RA) (diaphragm sparing supraclavicular block (SCB)) edges over general anesthesia (GA), as the manipulation of the cervical spine could be avoided and it also provides stable cardiac and respiratory dynamics. In this case report, we are discussing about a case of conservatively managed ACSCI posted for left humerus plating. We conclude that ultrasound-guided diaphragm sparing SCB is a safe alternative to GA for ACSCI patients posted for upper limb surgeries in neurogenic shock.